KINERJA VOIP SIP DAN VOIP H.323 - Maulidya, Siti Imsyawati (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
Development of voice over internet protocol technology is so fast because of computer and internet technology. The development of VoIP is caused by high cost of communication using PSTN line telephone. Then an idea to change voice traffic to computer net which is cheaper appears. To communicate using VoIP needs some protocols. The first major protocol is signal protocol that function as starting, managing, and ending the communication. Some examples of signal protocols are 11.323 from ITU-T, and Session Initiation Protocol (SIP) from IETF. Both can serve VoIP with different ways. SIP is text based, whereas 11.323 is binary based. Although as general both protocols have the same performances in developing VoIP application, communication quality depends on client program used, code, hardware configuration, and net condition.